Kajian An Abridged Malay-English Dictionary susunan R.J. Wilkinson dari sudut etimologi (Jurnal Bahasa, 2009)
Etymological studies in Malay Language are rather scarce compared to other studies. Aspiring researchers shy away from research work on etymological projects probably due to lack of old documents and materials. Perhaps, one of excellent sources for etymological studies is old dictionaries compiled centuries ago. As such, this etymological study is an attempt to study an old document, "An Abridged English-Malay Dictionary " a bilingual dictionary compiled by R.J. Wilkinson a hundred years ago. This study looks at the etymological information provided in this old dictionary. Among the information scrutinized are the origins of most borrowed words in Malay changes in the form of the words compared with the latest standard form, and also the change of meanings of these words over the years. It is hyped that the information retrieved from this old document could provide some etymological insights towards Malay Studies.